Mediation Role of Satisfaction in the Influence of Experiential Marketing on Word of Mouth on Sharia Bank Customers - Rudi Yacuub; M. Iqbal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine how the mediating role of satisfaction in the influence of experiential marketing on word of mouth on Islamic bank customers. This study uses a quantitative method with a questionnaire as a research instrument. The population in this study were 130 customers of BSI KC Palembang Demang using the accidental sampling method. The results show that experiential marketing has a positive impact on satisfaction, satisfaction has a positive impact on word of mouth, and experiential marketing has a positive impact on word of mouth, and satisfaction successfully mediates experiential marketing on word of mouth.